COMPARATIVE STUDY ON THE NUTRITIVE VALUES OF SILAGE PRODUCED FROM NAPIER GRASS (Pennisetum purpureum) VARIETIES IN SHIKA, NIGERIA - Y.M., Ishiaku; I, Ramatu (Kashere Journal of Animal Science, 2025)
Seasonal feed scarcity is a major constraint to sustainable livestock production in tropical regions. Ensiling surplus forage is a key strategy to mitigate this issue. This study evaluated the nutritive value and fermentation characteristics of silage produced from four Napier grass varieties (Juncao, Super Napier, Hybrid Napier, and Elephant grass) cultivated in Shika, Nigeria. A Randomized Complete Block Design (RCBD) with three replications was used. The grasses were harvested at 10 weeks, chopped, and ensiled for 22 days using a bottle silo method. Silage samples were analyzed for physical properties, proximate composition, fiber fractions, and mineral content. Results indicated significant differences (p<0.05) among varieties. Super Napier grass silage had the lowest pH value of (3.93), Hybrid Napier and Elephant grass silages had pH values of 4.11 and 4.17 respectively, which are within the optimal range (pH < 4.2) for well-preserved silage, indicating efficient lactic acid production and inhibition of spoilage microorganisms and very sweet aromas. Elephant grass recorded the highest crude protein (12.07%) but also the highest fiber fractions (ADF 35.75%, NDF 69.32%), potentially limiting its digestibility. Juncao grass showed the most favorable fiber profile for intake (lowest NDF: 66.35%) and the highest phosphorus content (1.32%). It is concluded that while Hybrid Napier offers a balanced combination of good fermentation quality and moderate nutrient levels, Juncao grass presents exceptional potential as a mineral-rich, highly digestible silage source. The choice of variety should be based on specific nutritional goals and supplementation strategies.